Physiological roles of glucocorticoids during early embryonic development of the zebrafish (Danio rerio). (25th November 2013) - Wilson, K. S.; Matrone, G.; Livingstone, D. E. W.; Al‐Dujaili, E. A. S.; Mullins, J. J.; Tucker, C. S.; Hadoke, P. W. F.; Kenyon, C. J.; Denvir, M. A.
Key points Glucocorticoids are known to be present in the developing zebrafish embryo but little is known about their physiological role at this early stage. The zebrafish embryo demonstrates a functional glucocorticoid system from around 48 h post fertilisation. This system and the stress response is amenable to pharmacological and genetic manipulation in a manner predicted by mammalian physiology. Glucocorticoids play a key developmental role in hatching, swimming and stress response. The zebrafish embryo is a relevant model for the study of glucocorticoid physiology. Abstract While glucocorticoids (GCs) are known to be present in the zebrafish embryo, little is known about their physiological roles at this stage. We hypothesised that GCs play key roles in stress response, hatching and swim activity during early development. To test this, whole embryo cortisol (WEC) and corticosteroid‐related genes were measured in embryos from 6 to 120 h post fertilisation (hpf) by enzyme linked immunosorbent assay (ELISA) and quantitative real‐time polymerase chain reaction (qRT‐PCR). Stress response was assessed by change in WEC following stirring, hypoxia or brief electrical impulses applied to the bathing water. The impact of pharmacological and molecular GC manipulation on the stress response, spontaneous hatching and swim activity at different stages of development was also assessed. WEC levels demonstrated a biphasic pattern during development with a decrease from 0 to 36 hpf followed by a progressive increase towards 120 hpf. This was accompanied by a significant and sustained increase in the expression of genes encoding cyp11b1 (GC biosynthesis), hsd11b2 (GC metabolism) and gr (GC receptor) from 48 to 120 hpf. Metyrapone (Met), an inhibitor of 11β‐hydroxylase (encoded by cyp11b1), and cyp11b1 morpholino (Mo) knockdown significantly reduced basal and stress‐induced WEC levels at 72 and 120 hpf but not at 24 hpf. Spontaneous hatching and swim activity were significantly affected by manipulation of GC action from approximately 48 hpf onwards. We have identified a number of key roles of GCs in zebrafish embryos contributing to adaptive physiological responses under adverse conditions. The ability to alter GC action in the zebrafish embryo also highlights its potential value for GC research.